IMPLEMENTASI PELAYANAN ARSIP KELUARGA MELALUI PROGRAM ASTRAJINGGA (ANJUNGAN RESTORASI ARSIP TRENDING KELUARGA) DI DESA SINDANGPANON KABUPATEN PURWAKARTA - Naila Azizah, Syahnaz; Permana, Hinggil; Hadiansyah, Chairil Fajar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Archives are important documents that have legal, administrative, and historical value in human life. However, public awareness regarding the importance of family archives is still relatively low, causing many important documents to be damaged, lost, or not properly maintained. The Astrajingga Program (Anjungan Restorasi Arsip Trending Keluarga) initiated by the Department of Archives and Library of Purwakarta Regency is one of the archival service innovations aimed at increasing public awareness and protecting family archives through encapsulation services. This study aims to analyze the implementation of the Astrajingga Program in increasing public awareness regarding the importance of family archives in Sindangpanon Village, Purwakarta Regency. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of archival officers, village officials, and community members participating in the Astrajingga Program. The results showed that the implementation of the Astrajingga Program has been carried out quite well through socialization activities, archive restoration services, and direct assistance to the community. The program has a positive impact on increasing community understanding of the importance of protecting family archives. However, several obstacles were found, such as limited public awareness, limited service implementation time, and limited service coverage. Therefore, strengthening socialization, sustainable program implementation, and collaboration between the Archives Office and village government are needed to improve the quality of archival services to the community.